Weed Control in Carrot - Peter J. Dittmar; William M. Stall (EDIS)
Weeds reduce carrot yields by reducing the size of carrot roots through direct competition for nutrients, space, and water. Weeds also deform carrot roots, making them unmarketable. Weeds late in the season may also cause severe harvesting problems. This revised 3-page fact sheet was written by Peter J. Dittmar and William M. Stall, and published by the UF Department of Horticultural Sciences, June 2012.